1997
DOI: 10.1200/jco.1997.15.2.589
|View full text |Cite
|
Sign up to set email alerts
|

Eastern Cooperative Oncology Group phase II trial of ifosfamide in the treatment of previously treated advanced urothelial carcinoma.

Abstract: IFX has significant activity, but also major toxicity in a heavily cisplatin-pretreated cohort with advanced urothelial carcinoma. A modification of dose and/or schedule from that described should be considered in future trials. Combination regimens using this agent should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(82 citation statements)
references
References 15 publications
0
80
0
1
Order By: Relevance
“…Ifosfamide had been studied in the past, and its phase II results in previously treated patients (not all platinum pretreated) have been somewhat inconsistent with response rates of 1 and of 20% in two studies (Pronzato et al, 1997;Witte et al, 1997). Be that as it may, its use has become less frequent, due to the renal toxicity of Vinflunine salvage therapy for bladder cancer S Culine et al the compound, a particular problem with bladder carcinoma patients who have received prior platinum.…”
Section: Discussionmentioning
confidence: 99%
“…Ifosfamide had been studied in the past, and its phase II results in previously treated patients (not all platinum pretreated) have been somewhat inconsistent with response rates of 1 and of 20% in two studies (Pronzato et al, 1997;Witte et al, 1997). Be that as it may, its use has become less frequent, due to the renal toxicity of Vinflunine salvage therapy for bladder cancer S Culine et al the compound, a particular problem with bladder carcinoma patients who have received prior platinum.…”
Section: Discussionmentioning
confidence: 99%
“…In examining older agents, only ifosfamide seemed to have shown any promise in this subset of patients. In a phase ii trial, 56 cisplatinpretreated patients received ifosfamide and achieved an or of 20%, with a mds of 5.3 months 49 .…”
Section: Single-agent Second-line Therapymentioning
confidence: 99%
“…As a result, there is an expanding, albeit still modest, number of patients with advanced urothelial carcinoma who are fit enough to receive second-line chemotherapy. The 4,9,11,15,16 Witte et al performed a large Phase II trial of ifosfamide that demonstrated a response rate of 20%, with 5 patients obtaining a complete response. However, the toxicity associated with this therapy was not insignificant, with myelosuppression being problematic.…”
Section: Discussionmentioning
confidence: 99%
“…However, the toxicity associated with this therapy was not insignificant, with myelosuppression being problematic. 9 More recently, Lorusso et al administered gemcitabine at a dose of 1200 mg/m 2 weekly for 3 of 4 weeks in patients who previously were treated with cisplatin-based therapy and reported an overall response rate of 22.5%, with 4 patients (13%) achieving a complete response. 17 Albers et al treated cisplatin-refractory patients with gemcitabine, 1250 mg/m 2 , on Days 1 and 8 every 21 days and observed an 11% overall response rate with 2 of the responding patients (7%) obtaining a complete response.…”
Section: Discussionmentioning
confidence: 99%